Integrated Plasma and Bile Metabolomics Based on an UHPLC-Q/TOF-MS and Network Pharmacology Approach to Explore the Potential Mechanism of Schisandra chinensis-Protection From Acute Alcoholic Liver Injury - Su, Lianlin; Mao, Jing; Hao, Min; Lu, Tulin; Mao, Chunqin; Ji, De; Tong, Huangjin; Fei, Chenghao (Frontiers in Pharmacology, 2020)
SSchisandra chinensis (SC) is a well-known important traditional Chinese medicine (TCM), which has been used to treat liver disease in China for long time. But its overall effects and mechanism of action are unclear. The present study was to explore the potential mechanism of SC for protecting alcoholic liver injury (ALI). In this research, to do a full assessment of metabolic changes in ALI of Sprague-Dawley rats and to increase our understanding of physiological changes in normal and pathological states, ultra-high performance liquid chromatography combined with quadrupole time of flight mass spectrometry (UHPLC-Q/TOF-MS) was used to probe potential biomarkers to learn more about ALI and to evaluate the overall effect of SC for ALI in rats. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were used to investigate the global metabolomics alterations and to evaluate the therapeutic effects of SC in rats. Afterward, the component-target-pathway network of SC was constructed by the network pharmacology, thus liver injury-relevant signaling pathways were dissected and validate. The results manifested that SC has conspicuous therapeutic efficacy for ALI, which were suggested by the results of the pathological section and biochemical indexes assay, such as Alanine aminotransferase (ALT), Aspartate transaminase (AST), Alkaline phosphatase (AKP), γ-glutamyl transferase (γ-GT/GGT), Reactive oxygen species (ROS), Malondialdehyde (MDA). Furthermore, 21 kinds of potential biomarkers were identified in plasma samples and 20 kinds of potential biomarkers were identified in bile samples of ALI rats. They were mainly related to inflammation and dysfunction of amino acids and energy metabolism. The recovery of these interrupted access partly led to curative effect of SC on ALI.